Optimal design based on dynamic characteristics and experimental implementation of submersible electromagnetic actuators - Cai, Baoping (Strojniški vestnik, 2013)
An optimization procedure based on the dynamic characteristics of a submersible electromagnetic actuator constrained in a specific volume has been developed. In order to achieve the minimum response time and low vibration when the actuator is opened, five radial dimensions are optimized when the main limiting quantity is the maximum allowed temperature. Three models, including a thermal model, an electromagnetic model, and a mechanical model are constructed, and optimization calculation is performed by using Matlab/Simulink software. According to the optimization results, an actuator is manufactured and dynamic experiments are performed. The results show substantial agreement between experimental response times and simulated response times. In order to investigate the vibration when the actuator is opened and closed, vibration experiments of the actuator are also performed. The results show that the measured vertical and horizontal accelerations are near the calculated acceleration of the plunger. Both of the experiments show that the optimization procedure is sufficiently accurate, and the optimal submersible electromagnetic actuator is sufficiently secure to be used in subsea BOP stacks.
Keywords: dinamične lastnosti; dynamic characteristics; magnetic equivalent circuit; magnetni ekvivalentni tokokrog; optimal design; optimalna zasnova; potopni elektromagnetni aktuatorji; submersible electromagnetic actuator